مساهمة الرسم على النشاط المهني في تمويل ميزانية بلدية المسيلة - حجار ،مبروكة (جامعة الوادي University of Eloued, 2024)
تهدف الدراسة إلى تحليل الايرادات المتأتية من الرسم على النشاط المهني وأهميته في تعزيز الموارد المالية لبلدية المسيلة(الجزائر) خلال الفترة 2020-2023، مع تقييم مدى قدرة الرسم المحلي للتضامن على مليء الفراغ المالي المحتمل بعد إلغاء الرسم على النشاط المهني في إطار قانون المالية لسنة 2024، استخدمت الدراسة المنهج الوصفي التحليلي ، وأظهرت النتائج أن الرسم على النشاط المهني حقق ايرادات جيدة خلال فترة الدراسة، كما يعتبر الرسم المحلي للتضامن بديلا واعدا لتحقيق تمويل مستدام لميزانية البلديات إذا تم تصميمه وتنفيذه بعناية. This researchfocuses on studying the revenues generated by the professionalactivitytax and itsrole in strengthening thefinancialresources of the Municipality of M’sila (Algeria) during the period 2020- 2023.Additionally it evaluates the potential of the local solidarity tax to offset the financial shortfall following the abolishment of the professional activity tax according to the 2024 finance law, The study used a descriptiveanalytical approach, and the results showed that the Professional Activity Tax achieved good revenues during the study period. Moreover, the Local Solidarity Tax considered a promising alternative for ensuring sustainable funding for municipal budgets, if it is carefully designed andimplemented.
Contribution of the Professional Activity Tax to Financing the Budget of the Municipality of M'Sila During the Period 2020-2023: A Comparative Study with the Local Solidarity Tax as an Alternative
Keywords: رسم على نشاط مهني; رسم محلي للتضامن; Professional Activity Tax; Local Solidarity Tax; Municipality